2021
DOI: 10.1136/jitc-2020-002305
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived lactate inhibit the efficacy of lenvatinib through regulating PD-L1 expression on neutrophil in hepatocellular carcinoma

Abstract: BackgroundNeutrophils play a controversial role in tumor development. The function of programmed cell death-1 ligand (PD-L1+) neutrophils, however, may inhibit the cytotoxicity of anti-tumor immunity. In this study, we elucidate the stimulators of PD-L1+ neutrophils in tumor microenvironment (TME) and explore the optimal combination to enhance the effect of lenvatinib by inhibiting PD-L1+ neutrophils in hepatocellular carcinoma.MethodsNeutrophil infiltration after lenvatinib treatment was examined with RNA seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 43 publications
2
43
0
Order By: Relevance
“…Adachi et al held that the increase of PD-L1 will enhance the effect of PD-1 inhibitors (66). Lenvatinib also increased neutrophil and upregulated PD-L1 expression on neutrophils in the TME (77). In conclusion, the effect of lenvatinib on PD-L1 expression remains controversial and has not been finalized.…”
Section: Studies On the Mechanisms Of Lenvatinib Combined With Pd-1 I...mentioning
confidence: 99%
“…Adachi et al held that the increase of PD-L1 will enhance the effect of PD-1 inhibitors (66). Lenvatinib also increased neutrophil and upregulated PD-L1 expression on neutrophils in the TME (77). In conclusion, the effect of lenvatinib on PD-L1 expression remains controversial and has not been finalized.…”
Section: Studies On the Mechanisms Of Lenvatinib Combined With Pd-1 I...mentioning
confidence: 99%
“…6C). NF-Κb/Cox-2 pathway are reported to be associated with PD-L1 expression regulated by lactic acid [11]. The western blot results showed that lactate dehydrogenase A (LDHA), NF-Κb and Cox-2 expressions in LECs were signi cantly decreased after combined therapy (Fig.…”
Section: Dual Fgfr and Vegfr Inhibition Improve Anti-tumor Immunity T...mentioning
confidence: 92%
“…Under steady-state conditions, LECs express high levels of T-cell inhibitory molecules including PD-L1 (CD274), which inducing apoptosis in tumorspeci c CD8 + T cells [9]. Many studies have revealed that lactic acid, the ultimate down-stream metabolite of anaerobic glycolysis, was responsible for driving PD-L1 expression [10,11]. Strikingly, lymphangiogenesis involving robust sprouting, migration and proliferation of LECs are heavily rely on anaerobic glycolysis for ATP production [12].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of lactate in the TME promote differentiation of tumor-associated macrophages to the M2 subtype, while activated macrophages facilitate tumor invasion through the CCL17/CCR4/mTORC1 signaling axis ( Zhang et al, 2021 ). Lactate-induced PD-L1 up-regulation on neutrophils impairs T cell cytotoxicity in HCC ( Deng et al, 2021 ). In addition, tumor cell-derived lactate induces the expression of GPR81 in dendritic cells via paracrine mode to inhibit the antigen presentation function of immune cells ( Brown et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%